MENINGKATKAN AKTIVITAS DAN KREATIVITAS SISWA PADA MUATAN IPA MENGGUNAKAN MODEL BINTANG DI SEKOLAH DASAR - Rifka Zuhairiah, Aliza; Riandy Agusta, Akhmad (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
The problem in this research is the low level of student activity and creativity in science learning. The solution to overcome this problem is to use the BINTANG model, which is implemented in the learning process. This research uses a type of classroom action research (CAR) with the approach in this research being quantitative and qualitative. The research results showed that teacher activity obtained a percentage of 95% with the criteria